2007
DOI: 10.1038/ng2108
|View full text |Cite
|
Sign up to set email alerts
|

A QTL influencing F cell production maps to a gene encoding a zinc-finger protein on chromosome 2p15

Abstract: F cells measure the presence of fetal hemoglobin, a heritable quantitative trait in adults that accounts for substantial phenotypic diversity of sickle cell disease and beta thalassemia. We applied a genome-wide association mapping strategy to individuals with contrasting extreme trait values and mapped a new F cell quantitative trait locus to BCL11A, which encodes a zinc-finger protein, on chromosome 2p15. The 2p15 BCL11A quantitative trait locus accounts for 15.1% of the trait variance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
388
3
11

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 481 publications
(412 citation statements)
references
References 14 publications
10
388
3
11
Order By: Relevance
“…In contrast, a number of cis or transacting elements influence output of the g-globin genes, raising HbF and ameliorating the phenotype of transfusion dependent b-thalassemia [22]. Interestingly, HbF elevation has been mapped to loci located both inside (the XmnI polymorphism 5' to the Gg-globin gene) and outside the bglobin gene cluster by family and linkage studies [22,23]. More recently, the technique of genome wide association studies (GWAS) has been used to confirm the importance of 2 previously identified loci.…”
Section: Genetic Modifiersmentioning
confidence: 99%
“…In contrast, a number of cis or transacting elements influence output of the g-globin genes, raising HbF and ameliorating the phenotype of transfusion dependent b-thalassemia [22]. Interestingly, HbF elevation has been mapped to loci located both inside (the XmnI polymorphism 5' to the Gg-globin gene) and outside the bglobin gene cluster by family and linkage studies [22,23]. More recently, the technique of genome wide association studies (GWAS) has been used to confirm the importance of 2 previously identified loci.…”
Section: Genetic Modifiersmentioning
confidence: 99%
“…The 2p15 is a new locus mapping to the gene encoding the CH2-type zincfinger protein BCL11A on chromosome 2p15 [38]. It was suggested that deregulated BCL11A expression may influence F-cell production by affecting the kinetics of erythropoiesis [38]. These observations have been confirmed through the analysis of single nucleotide polymorphisms at the level of the 2p15 locus and F-cell production in a population of Sardinian β-thalassemic patients.…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 92%
“…Thus, Menzel et al genotyped 179 unrelated individuals from the extreme upper and lower tails of the F-cell distribution, drawn from a database of 5,184 phenotyped individuals from an adult twin registry. In addition to 6q23, they identified two additional QTLs on chromosomes 2p15 and 11p15 [38]. The 2p15 is a new locus mapping to the gene encoding the CH2-type zincfinger protein BCL11A on chromosome 2p15 [38].…”
Section: Regulation Of γ-Globin Gene Expressionmentioning
confidence: 99%
See 1 more Smart Citation
“…L'étude sur quatre généra-tions d'une grande famille indienne a révélé un QTL en 6q23, localisé entre les gènes HBS1L et c-MYB, qu'on a appelé polymorphisme intergénique HBS1L-MYB (HMIP) [5]. La recherche sur la totalité du génome a identifié en 2p15 un polymorphisme dans l'IVS2 (intervening sequence) de l'oncogène BCL11A, codant une protéine à doigts de zinc [6]. Ce dernier QTL a depuis lors été retrouvé dans 3 populations différentes [7].…”
Section: Association Entre Polymorphismes Génétiques Et Taux D'hbfunclassified